1968
DOI: 10.1098/rspa.1968.0199
|View full text |Cite
|
Sign up to set email alerts
|

Single crystal laser Raman spectroscopy

Abstract: The chemical implications of single crystal Raman spectroscopy by means of laser excitation are briefly outlined. Unambiguous assignments are presented for PdCl 2- 4 , PtCl 2- 4 , PtCl 2- 6 , PdCl 2- 6 , GeCl 2- 6 and TeCl 2- 6 species. Detailed scattering equations are applied to mercurous chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1971
1971
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…The well-defined Raman spectra between 80 and 700 cm –1 are characteristic of the anatase phase for NTO thin films, as shown in Figure . All films show similar peaks appearing around 144, 197, 399, 513, and 639 cm –1 , which correspond to three Raman modes of anatase TiO 2 . Raman experiments further confirm that NTO thin films do not exhibit any structural phase transition from anatase to rutile, and no NbO x phases are observed either. This is in good agreement with our XRD analysis.…”
Section: Resultsmentioning
confidence: 52%
“…The well-defined Raman spectra between 80 and 700 cm –1 are characteristic of the anatase phase for NTO thin films, as shown in Figure . All films show similar peaks appearing around 144, 197, 399, 513, and 639 cm –1 , which correspond to three Raman modes of anatase TiO 2 . Raman experiments further confirm that NTO thin films do not exhibit any structural phase transition from anatase to rutile, and no NbO x phases are observed either. This is in good agreement with our XRD analysis.…”
Section: Resultsmentioning
confidence: 52%
“…As X-ray diffraction did not provide conclusive information on the nature of titanium species existing in the solids, these were studied by Raman spectroscopy. The spectra ( Figure 2) showed that sample MTi1 was composed of both anatase and rutile phases, while sample MTi2 contained only anatase [29,30]. Considering that both samples were calcined under identical conditions, these results suggested that the crystallization of TiO 2 phases depended on the way the titanium precursor was reacted with montmorillonite.…”
Section: Resultsmentioning
confidence: 91%
“…In fact, Tobin (32) has cautioned that polarizabilities obtained from Raman experiments with crystals pertain to the crystal and not to the individual molecules. In general, only the frequencies (and not the intensities) can be relied on to reflect the Raman properties of the free molecule (33). Further, since the S-S stretch occurs at low frequency (about 500 cm-'), this internal mode of the molecule may couple with an overtone of a lattice mode in the crystal.…”
Section: Discussionmentioning
confidence: 99%